Novel compounds as potential anti-dengue therapies verified via inhibition of human hexokinase isoform II - Tanbin, Suriyea; Ahmad Fuad, Fazia Adyani (2020)
Dengue is one of the most fatal diseases in the world, which is caused by dengue virus (DENV). It has been reported that a glycolytic enzyme, namely the human hexokinase II (HKII) has a significant role in supporting viral replication in the host cell, thus the enzyme has been proposed as a drug target. The main aim of this research is to discover novel antidengue agents for the treatment of dengue infection through in silico screening and HKII enzymatic inhibition studies. Initially, potential inhibitors were screened from computational drug design experiments and evaluations of the potency of these compounds were executed through experimental work involving enzyme and DENV glycolytic enzyme inhibition assay. The selected compounds; such as chitin, 4R,5R-9-[(2S,3R,4S,5S)-3,4-dihydroxy-5 (hydroxymethyl) tetrahydrofuran-2-yl]-4,5-dihydro-1H-purin 6, 3-Fluoro-3-deoxy-Dglucopyranose and daidzin, which are the analogues of the original HKII ligands, exhibited effects on HKII’s enzymatic activity, with remaining activities of 63.68%,70.42%,85.09% and 65.15%, respectively, compared to HKII’s activity in the absence of any inhibitors. Among the mentioned inhibitors, chitin and daidzin have shown better inhibition, compared to the other compounds. Subsequently, these inhibitors were tested through viral inhibition assay using human Dermal Fibroblast cell infected with DENV-2 serotypes, where the multiplicity of infection was 0.5 (MOI). The cytopathic effect of the cell was observed after 48h of incubation period, where reduction of virus was measured using real time qRT -PCR method. Chitin has shown significant viral load of 3.249×105 cell/ml, which corresponds to 23.3% viral reduction with non-toxic effect at 32µM of inhibitor concentration, which correlated well with the earlier HKII inhibition assay. The rest of the inhibitors are under experiments. In conclusion, selected inhibitors that were obtained from virtual screening analyses have great potentials as potent HKII and DENV inhibitors, which can further be developed as future anti-dengue therapeutics.